Lexical-constructional Subsumption Processes in the Lexical Constructional Model: The Case of Join and Attach - Rodríguez-Juárez, Carolina (Miscelánea: A Journal of English and American Studies, 2014)
This article presents the results of the study of the verbs of position join and attach, as members of the verbal subdomain “putting things together” (Faber and Mairal 1999), taking as a basis the theoretical and methodological assumptions of Role and Reference Grammar (Van Valin and Lapolla 1997; Van Valin 2005), and the tenets of the Lexical Constructional Model, as outlined in Ruiz de Mendoza and Mairal (2007a/b, 2008) and Mairal and Ruiz de Mendoza (2006, 2008, 2009a/b). In order to account for the relationship between lexical meaning and syntactic representation, we will first provide the semantic and syntactic information of these verbs which will allow us to propose their lexical templates and explore the constraints which might condition the process of lexical-constructional subsumption at the core grammar level of description, and which might lead to the fusion of low-level lexical templates into higher level-constructional patterns such as the resultative construction.